Analysis of Students' Attitudes and Difficulties in Studying Computational Physics - Revi Indriani; Akmam Akmam; Fatni Mufit; Rahmat Hidayat; Silvi Yulia Sari (Universitas Lambung Mangkurat, 2022)
Ideally, students who study Computational Physics are required to think computationally. However, student learning outcomes tend to be low. Low learning outcomes are suspected by students having difficulties. One of the causes of learning difficulties is students' attitude in responding to learning. This study aims to determine student attitudes in studying Computational Physics and the factors influencing student learning difficulties. This research is descriptive research with a quantitative approach. The population in this study were students of Physics FMIPA UNP. The sample in this research is students who take Computational Physics courses in January-June 2021. The data analysis technique used is the multivariate analysis based on factor loading testing with Confirmatory Factor Analysis (CFA) using Lisrel 8.80. The results showed that students' attitudes toward Computational Physics were good, with a percentage of student responses of 67.16%. Factors that influence learning difficulties are internal factors in the form of psychological factors in the aspect of interest (65%), motivational aspects (58%), and aspects of study habits (49%). Meanwhile, external factors do not affect students' difficulties in studying Computational Physics. Further research, it is necessary to carry out a similar analysis by taking into account other factors that are thought to influence the attitudes and difficulties of students in studying Computational Physics, both internal and external factors, so that they are better in determining the next steps to overcome student difficulties in studying Computational Physics.